1999
DOI: 10.1590/s0100-879x1999000200005
|View full text |Cite
|
Sign up to set email alerts
|

Poly-DL-lactide-co-glycolide microspheres as a controlled release antigen delivery system

Abstract: Successful vaccine application means maximum protection with minimal number of administrations. A rational development of vaccines involves studies of the nature of the antigen as well as of the adjuvant to be used to improve the immune responses. This has provided the impetus for studies to design the degradable devices and for different approaches to antigen delivery by different routes of administration. The development of controlled release systems based on polymeric devices that permit a sustained or puls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0
5

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 52 publications
2
36
0
5
Order By: Relevance
“…However, DNA-loaded microspheres were also unable to protect mice against challenge. 16 This inability to confer protection against challenge could be associated with the reduction of the DNA amount administered and, consequently, the reduction of immunostimulatory CpG motifs. Immunomodulatory properties as induction of cytokine production and costimulatory molecules expression have been attributed to CpG motifs.…”
Section: Introductionmentioning
confidence: 99%
“…However, DNA-loaded microspheres were also unable to protect mice against challenge. 16 This inability to confer protection against challenge could be associated with the reduction of the DNA amount administered and, consequently, the reduction of immunostimulatory CpG motifs. Immunomodulatory properties as induction of cytokine production and costimulatory molecules expression have been attributed to CpG motifs.…”
Section: Introductionmentioning
confidence: 99%
“…Biodegradable nanoparticles used as immune potentiators and delivery systems are now playing an increasing role in next-generation vaccine development projects. [36][37][38][39][40][41][42][43][44][45] Previously we showed that a PLGA-encapsulated rMOMP peptide induced Th1 responses in vitro which were potentiated by the presence of PLGA, 44 triggered expansion of T cell subsets and production of primarily rMOMP-specific Th1 cytokines in immunized mice; and sera from PLGA-rMOMP-immunized mice had increased levels of rMOMP-specific Th1 antibodies. One concern with encapsulating proteins in PLGA using the w/o/w emulsion is the generation of heat, which poses a major risk to proteins, and increases the chances of instability, degradation, and interaction with organic solvents.…”
Section: Discussionmentioning
confidence: 99%
“…[31][32][33][34][35] A promising alternative to using adjuvant is encapsulation of an immunogen in biodegradable polymers approved by the US Food and Drug Administration that release their contents over time. [36][37][38][39][40][41][42][43][44][45] Among the approved biodegradable polymers, poly D, L-lactide-co-glycolide (PLGA) nanoparticles have advantages that include enhancement of immune responses, delivery, biocompatibility and biodegradability, size, and sustained release. 38,43,44 Several studies have shown the efficiency of this release system when used to encapsulate other peptides, proteins, or DNA.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations